Mindanao the long journey to peace and prosperity - Hutchcroft, Paul D (Paul David) (World Scientific, 2018)
"Across more than four decades, the conflict between the national government and Muslim liberation forces in the southern Philippines has killed tens of thousands and displaced millions. Two landmark agreements under the presidency of Benigno S Aquino III--the first in 2012 and the second in 2014--raised high hopes that peace might finally be on the way. But the peace process stalled, and has yet to regain momentum, after a botched counterterrorism operation in early 2015. This volume provides both in-depth examination of the latest stage of a still-ongoing peace process as well as richly textured analysis of the historical, political, and economic context underlying one of the most enduring conflicts in the world"--